ARMA modelling and forecasting of monthly streamflows with application to the Angat reservoir inflows - Dizon, Cornelio Q.
A step-by-step procedure of ARMA model construction is presented and used to model and forecast the monthly inflows to the Angat Reservoir. Statistical properties (mean, standard deviation, correlation coefficient, standard forecast error, and peak forecast error) on the one-step-ahead forecast for the various competing ARMA models are computed in order to compare their actual performance and to check if their forecast preserved the statistical properties of the historical data.